PELUANG DAN TANTANGAN PENERAPAN PRINSIP SYARIAH DI INDUSTRI PERHOTELAN: STUDI KASUS HOTEL UNISI YOGYAKARTA - Indi Printianto; Dyah Wahyuning Tyas; Rosalina Nur Annisa (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2020)
Sharia hotels are hotels that implement Islamic sharia principles in all of their operational activities. The sharia principles in hospitality consist of six principles, among others, namely the principle of consumption, entertainment, business activities, ethical, boundary relations, and layout. This research is a descriptive qualitative field study that aims to find out the application of six sharia principles in Yogyakarta Unisi Hotel while analyzing the opportunities and challenges of sharia implementation in Yogyakarta Unisi Hotel. Primary data collection is done by interviews, focus group discussions, and hotel guest ratings through social media. The results showed that Unisi hotel has implemented five sharia principles in the field of hospitality, while one principle (the principle of entertainment) could not be investigated because it was not available in Unisi Hotel. In addition, the opportunity to develop Unisi hotel business is huge because it follows the